Bioactivity of dietary polyphenols: The role of metabolites - Luca, Simon Vlad; Macovei, Irina; Bujor, Alexandra; Miron, Anca; Skalicka-Woźniak, Krystyna; Aprotosoaie, Ana Clara; Trifan, Adriana (Critical reviews in food science and nutrition, 2020)
A polyphenol-rich diet protects against chronic pathologies by modulating numerous physiological processes, such as cellular redox potential, enzymatic activity, cell proliferation and signaling transduction pathways. However, polyphenols have a low oral bioavailability mainly due to an extensive biotransformation mediated by phase I and phase II reactions in enterocytes and liver but also by gut microbiota. Despite low oral bioavailability, most polyphenols proved significant biological effects which brought into attention the low bioavailability/high bioactivity paradox. In recent years, polyphenol metabolites have attracted great interest as many of them showed similar or higher intrinsic biological effects in comparison to the parent compounds. There is a huge body of literature reporting on the biological functions of polyphenol metabolites generated by phase I and phase II metabolic reactions and gut microbiota-mediated biotransformation. In this respect, the review highlights the pharmacokinetic fate of the major dietary polyphenols (resveratrol, curcumin, quercetin, rutin, genistein, daidzein, ellagitannins, proanthocyanidins) in order to further address the efficacy of biometabolites as compared to parent molecules. The present work strongly supports the contribution of metabolites to the health benefits of polyphenols, thus offering a better perspective in understanding the role played by dietary polyphenols in human health.